2005
DOI: 10.1177/0734904105049172
|View full text |Cite
|
Sign up to set email alerts
|

On Quantification of Error and Uncertainty in Two-zone Models used in Fire Safety Design

Abstract: The error in smoke transport models have mainly been analyzed with qualitative approaches till date. The results make it difficult to perform a quantitative assessment of the model error in fire safety design applications. Even if a model has a substantial model error, it can be a very useful tool, as long as the designer is aware of the errors and the uncertainties in the predictions. This paper presents a methodology to quantify the error in model predictions and the associated uncertainties with a statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…The simulation of a fire in a compartment is a complex phenomenon that is commonly simplified to two independent parts; first, the method by which the temperature produced by the fire is accounted for ( T gas ) and, second, the actual boundary condition that needs to be applied to the structural element. For the former, several parametric models have been developed to calculate the temperatures produced by a fire in a compartment (Remesh and Tan, ; Lundin, ). These models are established either using ‘time–temperature curve’ methods—sometimes called ‘standard fire’—such as those mentioned in ISO 834 International Standard (), and ASTM E119 () (based on experiment and tests) or using ‘natural fire’ models that rely mainly on the volume of the produced gas by the combustible materials in a space such as those stated in SEI/ASCE ().…”
Section: Methodsmentioning
confidence: 99%
“…The simulation of a fire in a compartment is a complex phenomenon that is commonly simplified to two independent parts; first, the method by which the temperature produced by the fire is accounted for ( T gas ) and, second, the actual boundary condition that needs to be applied to the structural element. For the former, several parametric models have been developed to calculate the temperatures produced by a fire in a compartment (Remesh and Tan, ; Lundin, ). These models are established either using ‘time–temperature curve’ methods—sometimes called ‘standard fire’—such as those mentioned in ISO 834 International Standard (), and ASTM E119 () (based on experiment and tests) or using ‘natural fire’ models that rely mainly on the volume of the produced gas by the combustible materials in a space such as those stated in SEI/ASCE ().…”
Section: Methodsmentioning
confidence: 99%
“…It has been found that the error varies both within a scenario and between different scenarios [3]. From a practical standpoint, it is crucial to reduce the complexity of adjusting for the error.…”
Section: Model Error In Two-zone Modelsmentioning
confidence: 99%
“…Since there is no generally accepted protocol for addressing uncertainties in model predictions with a quantified approach, the quantitative approach must be regarded as one of several recognized tools. Another objective is to evaluate whether the statistical analysis model, presented in depth by Lundin [3], is appropriate for this purpose.…”
Section: Objectivesmentioning
confidence: 99%
“…Several methods have been developed to calculate the thermal actions produced by a fire in a compartment (Lundin, ; Remesh and Tan, ). These methods have been established either using parametric fires called ‘time–temperature curves’, such as those mentioned in ISO834 (ISO 834 International Standard, ) and American Society for Testing and Materials (ASTM) E119 (ASTM, ) and based mainly on experiment and tests or using ‘natural fires’, which rely mainly on the volume of gas produced by the combustible materials in a covered space, such as those stipulated in the American Society of Civil Engineers or ASCE ().…”
Section: Computational Proceduresmentioning
confidence: 99%